Orienting to Emotion in Computer-Mediated Cognitive Behavioral Therapy. Issue 4 (1st October 2016) - Ekberg, Stuart; Shaw, Alison R. G.; Kessler, David S.; Malpass, Alice; Barnes, Rebecca K.
ABSTRACT: Exploring emotions is a defining feature of psychotherapy. This study explores how therapists orient to emotions when they cannot see or hear their clients. In analyzing 1, 279 sessions of online text-based Cognitive Behavioral Therapy (CBT), we focused on therapists' commiserations (e.g., "I'm sorry to hear that") and their affective inferences (e.g., "that sounds very scary for you"). Both practices routinely prefaced moves to pursue a range of therapeutic activities, many of which did not prioritize sustained focus on the emotion that had just been oriented to. By separating message composition from message transmission, the modality used for these therapy sessions enabled therapists to combine orientations to emotion with attempts to shift the focus of discussion. Our analysis finds that although physically co-present and computer-mediated psychotherapy share a common focus on emotional experience, the modality used for therapy can be relevant in the design and use of these orientations. Data are in British English.